Community-Based Tourism and Economic Growth: A Bibliometric Review and Analysis - Hidayat, Angger; Jumriatunnisah, Nur; Nugroho, Dhimas Setyo (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2026)
This study aims to comprehensively evaluate the performance and trends of scholarly publications regarding the impact of Community-Based Tourism (CBT) on economic growth through a bibliometric analysis. Despite the growing research interest in the economic dimensions of CBT over the last decade, there remains a significant gap in mapping the intellectual structure and bibliographic landscape of the literature produced to date. Utilizing 458 articles indexed in the Scopus database, the research employed Publish or Perish for data retrieval and VOSviewer for bibliometric mapping. The analysis encompasses publication growth, prominent authors, leading contributing countries and organizations, keyword co-occurrence, and co-authorship networks. The findings reveal the evolution of publication trends and identify both established and emerging research clusters. The analysis indicates a thematic shift from localized economic impacts toward the integration of sustainability and digital adaptation within the CBT framework. This study provides a foundational framework for understanding existing literature gaps. Future research is recommended to explore the integration of financial technology within CBT ecosystems and to conduct longitudinal analyses on the economic resilience of communities in a post-pandemic context, which remain underrepresented in current research clusters.